Predictive ability of shear wave elastography for pruritus in chronic hepatitis C patients with sustained virological response. Issue 9 (September 2018) - Tachi, Yoshihiko; Hirai, Takanori; Kojima, Yuko; Ishizu, Yoji; Honda, Takashi; Kuzuya, Teiji; Hayashi, Kazuhiko; Ishigami, Masatoshi; Goto, Hidemi; Katano, Yoshiaki
Abstract : Background and aims: Pruritus is one of the complications with chronic liver disease and markedly worsens quality of life. However, the current status of pruritus in chronic hepatitis C patients who have achieved a sustained virological response (SVR) has not been clarified sufficiently. The aim of this study was to investigate the predictors of pruritus in post-SVR patients treated with direct-acting antivirals (DAA). Patients and methods: In this retrospective study, we enrolled 110 hepatitis C patients with SVR who underwent serial shear wave elastography before DAA therapy and at the end of treatment. The severity of pruritus was evaluated using Kawashima's pruritus scores and a visual analog scale. Results: The prevalence of pruritus before treatment and after SVR was 28.2 and 25.5%. Multivariate logistic regression analysis confirmed that a history of hepatocellular carcinoma [odds ratio (OR): 9.72; 95% confidence interval (CI): 2.05–46.15; P =0.004], high γ-glutamyl transpeptidase levels at baseline (OR: 5.77; 95% CI: 1.83–18.21; P =0.003), low serum albumin at the end of treatment (OR: 4.85; 95% CI: 1.31–17.99; P =0.018), and high liver stiffness measurement assessed by shear wave elastography at the end of treatment (OR: 3.16; 95% CI: 1.19–11.01; P =0.024) were significant independent factors associated with pruritus in patients who had achieved an SVR following DAA therapy. Conclusions: In chronic hepatitis C patients with SVR after DAA therapy, the incidence of pruritus is not uncommon. Liver stiffness measurement is useful for predicting the incidence of pruritus. Thus, even if SVR is achieved, patients with higher liver stiffness at the end of treatment must be monitored carefully for pruritus.